Unraveling microbial life from a high-altitude hydrothermal system in the Andes plateau and their potential for nitrogen transformations - Pardo-Este, Coral; Castro-Severyn, Juan; Aldridge, Jacqueline; Alvarez-Saravia, Diego; Kurte, Lenka; Aguilar-Munoz, Polette; Paquis, Pablo; Perez, Vilma; Medina-Ortiz, David; Jeffrey, Wade H.; Molina, Veronica; Hengst, Martha (My University, 2025)
Terrestrial hydrothermal systems provide a window for studying the biogeochemical interactions that occur in hot and gas-rich ecosystems resembling the conditions found in early life on Earth. The biogeochemical dynamics of the Andean hydrothermal systems in the Atacama Desert area are still understudied. Thus, we aimed to characterize the taxonomic composition and genomic potential of nitrogen transformations in a microbial community inhabiting a high-altitude hydrothermal system on the Altiplano Plateau of the Chilean Andes. Specifically, we sampled sediment and microbial mats in three ponds with water temperatures ranging from 42 to 64 degrees C. We found a high prevalence of photoheterotrophs, with differences in taxonomic composition and gene abundance between the microbial communities found in the sediment and microbial mats. Changes in physicochemical conditions, such as temperature and pH, and the concentrations of CO2, CH4 and Mn accounted for the variability in the microbial community structure. Our results indicated an enrichment of N-related genes associated with nitrate reduction, denitrification, and ammonia assimilation, suggesting a metabolically versatile community using nitrate, nitrite, and gaseous nitrogen species to assimilate ammonia into their biomass. This study contributes to our understanding of the taxonomy and functional microbial dynamics in a high-altitude thermal system, where ammonia assimilation is potentially critical for biomass formation, and particular environmental conditions favor adaptations to maintain biogeochemical cycles.
Keywords: thermophiles; hydrothermal system; nitrogen cycle